2020
DOI: 10.1111/cmi.13260
|View full text |Cite
|
Sign up to set email alerts
|

The roles of tetraspanins in bacterial infections

Abstract: Tetraspanins, a wide family composed of 33 transmembrane proteins, are associated with different types of proteins through which they arbitrate important cellular processes such as fusion, adhesion, invasion, tissue differentiation and immunological responses. Tetraspanins share a comparable structural design, which consists of four hydrophobic transmembrane domains with cytoplasmic and extracellular loops. They cooperate with different proteins, including other tetraspanins, receptors or signalling proteins t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 98 publications
1
26
0
Order By: Relevance
“…Tetraspanins can interact with different types of proteins such as adhesion molecules, immunoglobulin, signaling receptors, intracellular signaling molecules and immune signaling molecules ( 3 , 6 ). Tetraspanins also can interact with lipids namely membrane gangliosides and cholesterol ( 3 , 7 ). The web of tetraspanins allows it to form larger downstream complexes.…”
Section: Tetraspaninsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tetraspanins can interact with different types of proteins such as adhesion molecules, immunoglobulin, signaling receptors, intracellular signaling molecules and immune signaling molecules ( 3 , 6 ). Tetraspanins also can interact with lipids namely membrane gangliosides and cholesterol ( 3 , 7 ). The web of tetraspanins allows it to form larger downstream complexes.…”
Section: Tetraspaninsmentioning
confidence: 99%
“…They are known to be the ‘gateway’ for infections through their TEM-dependent complexes at the EC2 region ( 5 , 11 ). Tetraspanins are utilised directly or indirectly by the pathogens to manipulate the normal cellular processes for pathogens binding, intracellular trafficking, replication, and infection development within the human cells ( 7 ). Tetraspanins are well documented to be associated with the hepatitis C virus and human immunodeficiency virus (HIV) for viral entry into the host cells ( 5 ).…”
Section: Tetraspaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetraspanins belong to a superfamily of glycoproteins, which span the membrane four times and possess a small (SEL) and a large extracellular loop (LEL). 22 These proteins display a wide panel of cellular functions (adhesion, motility, and fusion) and are related to infection by a variety of human pathogens, including viruses, parasites and bacteria. 22 Humans possess 33 tetraspanins, with most cells expressing simultaneously multiple members of this family of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Partner proteins can include integrins, HSPGs and immunoglobulin superfamily members (Umeda et al, 2020), many of which are important in host cell adherence and entry of microbial pathogens. The tetraspanins have been implicated in a number of different viral and bacterial infections (Florin and Lang, 2018; Karam et al, 2020). We have previously demonstrated that tetraspanin blockade, using antibodies or recombinant EC2 domains, can significantly reduce Gram-negative and Gram-positive bacterial adherence to epithelial cells (Green et al, 2011).…”
Section: Introductionmentioning
confidence: 99%